1975
DOI: 10.1111/j.1365-2222.1975.tb01864.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal betamethasone valerate in the treatment of seasonal rhinitis

Abstract: Summary Betamethasone valerate aerosol given in doses of 100 μg into each nostril twice daily was compared with a placebo in a double‐blind, cross‐over trial involving thirty patients with seasonal rhinitis. Patients recorded symptoms of eye irritation and watering, sneezing, rhinorrhoea, and nasal blockage, on a diary card. Analysis of the symptom scores showed that nasal symptoms were significantly better on betamethasone valerate than on placebo (P<0.01) and that nasal blockage in particular was improved (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Objective assessment of the features of rhinitis presents problems which have been discussed previously (Archer et al, 1975). Nasal airways resistance can be measured in the laboratory (Solomon et al, 1965;Jenssen, 1973) but a simpler technique using a peak How meter as described by Taylor et al (1973) encouraged us to try their method under trial conditions, with the patients taking their own readings at home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Objective assessment of the features of rhinitis presents problems which have been discussed previously (Archer et al, 1975). Nasal airways resistance can be measured in the laboratory (Solomon et al, 1965;Jenssen, 1973) but a simpler technique using a peak How meter as described by Taylor et al (1973) encouraged us to try their method under trial conditions, with the patients taking their own readings at home.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that intranasal betamethasone valerate and beclomethasone dipropionate are more effective than placebo in the treatment of both seasonal and perennial rhinitis (Mygind, 1973;Gibson et al, 1974;Archer, Thomas & Harding, 1975) but no comparison has been made between these steroids and conventional therapy in perennial rhinitis. In this study, betamethasone valerate aerosol (Bextasol), fitted with a nasal adaptor, is compared with the antihistamine and sympathomimetic combination-triprolidine 2-5 mg and pseudoephedrine 60 mg (Aetifed).…”
Section: Introductionmentioning
confidence: 99%
“…When fitted with an adapter (Fig. i), as used in the treatment of rhinitis (Archer, Thomas & Harding, 1975), this aerosol proved suitable for intra-oral use. The present investigation was designed to assess this novel form of treatment in oral lichen planus.…”
mentioning
confidence: 99%